Dampak Accrual Basic dan Sistem Pengendalian Intern Pemerintah terhadap Akuntabilitas kinerja Instansi Pemerintah - Mujennah Mujennah; Safriansyah Safriansyah; Iqbal Firdausi; Siti Fatimah (Owner : Riset dan Jurnal Akuntansi, 2022)
Researchers tested whether the application of accrual-based government accounting standards (SAP) as a form of GCG was able to improve the performance of government agencies KESBANGPOL through accrual-based SAP variables and a good internal control system was expected to be able to realize good governance. This study uses nine variables. Researchers distributed questionnaires to 47 employees of Kesbangpol Banjarmasin and tested the data through multiple regression analysis. The results showed that the accrual-based SAP implementation variables had an effect, and human resources, risk management, and supervision had a positive effect on AKIP. Variables of organizational commitment, information technology, control environment, control activities, information, and communication do not affect AKIP.